Taro Tube Flour Modification via Hydrogen Peroxide Oxidation - Catarina Sri Budiyati; Dessy Ariyanti (International Journal of Science and Engineering, 2014)
Colocasia esculentum (L) Schott known as “Talas bogor” in Indonesian language is easily grown in every island in Indonesia. It proved to have high content of carbohydrate as it can be utilize for wheat flour replacement in addition to prior modification using hydrogen peroxide. The objective of this research was to improve the quality of taro flour by assessing the effect of several parameter such as ratio of slurry, oxidation agent concentration, oxidation time and temperature. The result shows that using ratio of slurry 20% with 2% of H2O2 concentration in temperature of oxidation process 30oC and 60 min operation time can produced good quality of modified taro tube flour in terms of swelling power and water solubility with 7.2 g/g and 6.93% respectively. This condition has chosen by taking the technical and economic feasibility as consideration. This result also can be used as proof of evidence that using H2O2 as an oxidizing agent in the process of taro tube flour modification can improve the functional properties of the flour. As the swelling power and water solubility of original taro tube flour were 3.7 g/g and 1.8% respectively.